2007
DOI: 10.3746/jfn.2007.12.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Colostrum Basic Protein from Colostrum Whey Protein: Increases in Osteoblast Proliferation and Bone Metabolism

Abstract: Colostrum basic protein (CBP) (MW 1-30 kDa) were isolated from bovine colostrum using a series of ultrafiltration processes and their effects on osteoblast cell proliferation and bone metabolism were investigated in cell line and animal models. Treatment with CBP (1,10,100 µg/ml) does-dependently increased cell proliferation of osteoblastic MC3T3 cells. Alkaline phosphastase activity, a marker of osteoblased phenotype, in the cells was also increase after treatment with CBP in a does-dependent manner. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Physico-chemical characterisation of colostrum from human (Asakuma et al 2008;Jiménez et al 2008;Lee et al 2007;Maldonado-Barragán et al 2009), cow (Christiansen et al 2010;Tsioulpas et al 2007) and goat breeds (Argüello et al 2006;Górová et al 2011;Quiles et al 1991;Yang et al 2009) has been reported. The presence of high concentrations of nutrients such as proteins, vitamins, minerals, enzymes, antimicrobial peptides and immunoglobulins has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Physico-chemical characterisation of colostrum from human (Asakuma et al 2008;Jiménez et al 2008;Lee et al 2007;Maldonado-Barragán et al 2009), cow (Christiansen et al 2010;Tsioulpas et al 2007) and goat breeds (Argüello et al 2006;Górová et al 2011;Quiles et al 1991;Yang et al 2009) has been reported. The presence of high concentrations of nutrients such as proteins, vitamins, minerals, enzymes, antimicrobial peptides and immunoglobulins has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bovine colostrum has a high concentration of immune factors (Lee et al . ), which has led some authors to suggest the use of preparations from this product as a supplement in human healthcare (Alexieva et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro proliferation of murine splenic lymphocytes was stimulated by WP, but the effect was reduced following hydrolysis using a trypsin/chymotrypsin mixture [46]. In addition, WP increases osteoblast proliferation, as described by Lee et al [47]. Lymphocyte recirculation, which is critical for effective immunity, is tightly regulated by the expression of adhesion molecules and chemoattractant receptors on lymphocytes combined with the spatial and temporal expression of ligands for these receptors by a variety of tissue cells [48].…”
Section: Discussionmentioning
confidence: 88%